2019
DOI: 10.1080/10717544.2019.1618420
|View full text |Cite
|
Sign up to set email alerts
|

Development of synthetic high-density lipoprotein-based ApoA-I mimetic peptide-loaded docetaxel as a drug delivery nanocarrier for breast cancer chemotherapy

Abstract: In this study, a synthetic high-density lipoprotein (sHDL), peptide-based nanocarrier loaded with docetaxel (DTX) was constructed, against breast cancer. The thermodynamic and molecular dynamic analyses were conducted to examine the stability of nanoparticles synthesized from mimetic peptide 5 A and various types of phospholipids. Furthermore, the cellular uptake and in vivo fluorescence imaging analysis experiments, with scavenger receptor B-I (SR-BI) were carried out to examine the tumor-targeting ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Western blot analysis of MC38 cell lysate showed high expression of SR-B1 relative to actin band density. This SR-B1 expression level was comparable to that of other tumor cell lines with known increased expression of SR-B1 and a favorable response to SR-B1 targeted therapeutic strategies, such as B16F10 and 4T1 ( Figure 2A) [1,35,36]. We then examined sHDL uptake by MC38 cells in vitro ( Figure 2B).…”
Section: Sr-b1 Is Highly Expressed By Mc38 Cells and Plays A Role In supporting
confidence: 64%
See 1 more Smart Citation
“…Western blot analysis of MC38 cell lysate showed high expression of SR-B1 relative to actin band density. This SR-B1 expression level was comparable to that of other tumor cell lines with known increased expression of SR-B1 and a favorable response to SR-B1 targeted therapeutic strategies, such as B16F10 and 4T1 ( Figure 2A) [1,35,36]. We then examined sHDL uptake by MC38 cells in vitro ( Figure 2B).…”
Section: Sr-b1 Is Highly Expressed By Mc38 Cells and Plays A Role In supporting
confidence: 64%
“…Currently, the standard-of-care for patients with colon adenocarcinoma is surgery, radiation, chemotherapy, and possibly immunotherapy via immune checkpoint blockade. Though effective, both chemotherapy and immune checkpoint blockade agents are administered systemically and reach the tumor itself in very limited amounts [1]. Moreover, neither chemotherapy nor immune checkpoint blockade directly elicits immune memory against the tumor, which is crucial for preventing tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DTX-sHDL nanoparticles improved the uptake of docetaxel, augmented the cytotoxic effect against MCF-7 cells and reduced the toxicity to normal cells. Finally, in vivo experiments in 4T1 tumour-bearing mice showed superior tumour growth inhibition by DTX-sHDL nanoparticles than that of the free docetaxel-treated group [ 156 ]. Another study reported the design of a peptide-functionalized dual-targeting delivery system encapsulating paclitaxel and GANT61 in tLyP-1 peptide-modified reconstituted high-density lipoprotein nanoparticles (tLyP-1-rHDL-PTX/GANT61 nanoparticles), which may show potential when used in combination with conventional chemotherapy for treating metastatic triple-negative breast cancer.…”
Section: Breast Cancer In the Era Of Nanomedicinementioning
confidence: 99%
“…Observed under fluorescence microscope shown in Figure 11, coumarin 6 labeled d-rHDL (Figure 11(D-F)) and m-d-rHDL (Figure 11(G-I)) by bEND.3 cells had much stronger fluorescent intensity compared with lipid core without apoA-I and mA involved (Figure 11(A-C)) at all the corresponding times, about 1.32-fold and 2.46-fold more than that of lipid core at 4 h, respectively (Figure 13(A)). This may be due to the brain-targeting property of apoA-I anchored on the surface of rHDL associated with SR-BI specifically expressed on brain microvascular endothelial cells (Gong et al, 2019). It suggested that the uptake of nanoparticles in bEND.3 cells could be improved by the binding with apoA-I.…”
Section: Cell Uptake Studymentioning
confidence: 99%